Communication tool to promote breastfeeding in the context of Covid-19 (Research, Society and Development, 2022)
Breastfeeding is a millennial act that brings numerous benefits to the mother and child binomial. From this perspective, it is the duty of health professionals to protect, promote and support this practice, however, despite such efforts, it can have a number of difficulties. This is aggravated by the Covid-19 pandemic. In this context, health technologies are essential tools, because they allow optimizing care, empowering professionals quickly. Therefore, this work aims to build a communication tool for the promotion of breastfeeding in the context of the Covid-19 pandemic. This is a study with quantitative and qualitative methodological research, which was conducted in a Basic Health Unit, in the city of São Paulo - SP. The study occurred in 4 stages, including bibliographic review, situational diagnosis, proposal elaboration and technology construction. It is notepoint that professionals have limited knowledge about breastfeeding and that this worsens when the understanding of recommendations on lactation in times of pandemic is verified. From this, a visual audio technology was constructed lasting 3 minutes and 30 seconds in shades of gold and pink on the information about breastfeeding care during the pandemic. It is verified, therefore, that the proposed technology has the positive potential in the community from its dissemination in the digital environment with high coverage without territorial limits, enabling a positive impact on maternal and child care. We highlight the need to build technologies that contribute to clarifying the new epidemics worldwide.